Two years' effect of dimethyl fumarate on focal and diffuse gray matter pathology in multiple sclerosis. (November 2022) - Marastoni, Damiano; Crescenzo, Francesco; Pisani, Anna I; Zuco, Carmela; Schiavi, Gianmarco; Benedetti, Giulia; Ricciardi, Giuseppe K; Montemezzi, Stefania; Pizzini, Francesca B; Tamanti, Agnese; Calabrese, Massimiliano
Background: Data on the effect of dimethyl fumarate (DMF) on focal and diffuse gray matter (GM) damage, a relevant pathological substrate of multiple sclerosis (MS)-related disability are lacking. Objective: To evaluate the DMF effect on cortical lesions (CLs) accumulation and global and regional GM atrophy in subjects with relapsing–remitting MS. Methods: A total of 148 patients (mean age 38.1 ± 9.7 years) treated with DMF ended a 2-year longitudinal study. All underwent regular Expanded Disability Status Scale (EDSS assessment), and at least two 3T-magnetic resonance imaging (MRI) at 3 and 24 months after DMF initiation. CLs and changes in global and regional atrophy of several brain regions were compared with 47 untreated age and sex-matched patients. Results: DMF-treated patients showed lower CLs accumulation (median 0[0–3] vs 2[0–7], p < 0.001) with respect to controls. Global cortical thickness ( p < 0.001) and regional thickness and volume were lower in treated group (cerebellum, hippocampus, caudate, and putamen: p < 0.001; thalamus p = 0.03). Lower relapse rate (14% vs 40%, p < 0.001), EDSS change (0.2 ± 0.4 vs 0.4 ± 0.9, p < 0.001), and new WM lesions (median 0[0–5] vs 2[0–6], p < 0.001) were reported. No severe adverse drug reactions occurred. Conclusions: Beyond the well-known effect on disease activity, these results provide evidence of the effect of DMF through reduced progression of focal and diffuse GM damage.